Implant Supported Mandibular Overdenture: A Viable Treatment Option for Edentulous Mandible - Lambade, Dipti (JCDR Research and Publications (P) Limited, 2014)
The prosthetic management of the edentulous patient has long been a major challenge. Complete maxillary and mandibular dentures have been the traditional standard of care. However, most of the patients report problems adapting to their mandibular denture due to a lack of comfort, retention, stability and inability to masticate. Implant-supported overdentures have been a common treatment for edentulous patients for the past 20 years and predictably achieve good clinical results. Implant supported overdentures offer many practical advantages over conventional complete dentures and removable partial dentures. These include decreased bone resorption, reduced prosthesis movement, better esthetics, improved tooth position, better occlusion, increased occlusal function and maintenance of the occlusal vertical dimension. This article presents a design and fabrication technique of the implant-retained overdenture that uses four freestanding mandibular implants.